2012
DOI: 10.1088/0953-8984/24/37/376003
|View full text |Cite
|
Sign up to set email alerts
|

Spin glass behaviour and extrinsic origin of magnetodielectric effect in non-multiferroic La2NiMnO6nanoparticles

Abstract: We report magnetization, dielectric and dc transport properties of La(2)NiMnO(6) nanoparticles. Both dc and ac magnetization measurements indicated a metastable magnetic behaviour with random ferromagnetic and antiferromagnetic interactions below 110 K; critical slow-down, memory and rejuvenation properties signify the spin glass nature. The dc resistivity shows a semiconducting nature but the temperature dependent magnetoresistance (MR) shows a peak at the spin glass transition. The colossal dielectric proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 32 publications
2
47
3
Order By: Relevance
“…Further, this peak shifts systematically towards lower frequency side (see inset (i)) which points towards the presence of field induced dipolar relaxation. 24 It should be noted that all the measurements reported here, were repeated; the data and the observed difference in the magnetodielectric measurements are found to be consistent and well above the estimated error bar.…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…Further, this peak shifts systematically towards lower frequency side (see inset (i)) which points towards the presence of field induced dipolar relaxation. 24 It should be noted that all the measurements reported here, were repeated; the data and the observed difference in the magnetodielectric measurements are found to be consistent and well above the estimated error bar.…”
Section: Methodssupporting
confidence: 75%
“…20,21 However G. Catalan 22 and Jang et al 23 provided the way to establish whether the observed MD effect is that of the intrinsic character of the sample or due to magnetoresistive effects or due to heterogeneous character of the sample. 24 Keeping above in view, here, we present the room temperature MD studies on Mn doped LaGaO 3 . It should be noted that pure LaGaO 3 is a well known dielectric material with very low value of dielectric loss.…”
mentioning
confidence: 99%
“…Generally, relaxors contain permanent electrical dipoles in nanoscale region and the loss tangent (tand) peak position coincides with 00 peak position. 36,37 While previous reports suggest a relaxor-like behaviour for Nd 2 NiMnO 6 , 27,38 a large temperature separation is observed between the peak positions of 00 and (tand), as shown in the inset of Fig. 7(b).…”
Section: Resultsmentioning
confidence: 62%
“…[11][12][13] In these systems, the ferromagnetic (FM) property is governed by Goodenough-Kanamori 180 superexchange interactions among the B-site cations. 11,[15][16][17][18] Recently, Chandrasekhar et al have reviewed the effect of dimensionality on the magnetic transition and MD behaviour. The ordering depends on the synthesis conditions, doping on La or B 0 /B 00 sites and particle size.…”
Section: Introductionmentioning
confidence: 99%